A clinico-pathological study of thyroid nodules and correlation among ultrasonographic, cytologic, and histologic findings - Rajarshi Sannigrahi; Ganesh Chandra Gayen; Ray, Ritam (Asian Journal of Medical Sciences, 2023)
Background: Nodular thyroid is a common occurrence affecting 5% of the population. Aims and Objectives: To find the prevalence of thyroid nodules, to study the clinico-biochemical profile of the patients with thyroid nodules and to establish a correlation between pre-operative ultrasonography and fine-needle aspiration cytology (FNAC) with post-operative histopathologic findings. Materials and Methods: A prospective observational study was conducted in a tertiary care hospital in Kolkata over 1.5 years. Patients with clinically detectable nodules posted for surgery were evaluated clinically, biochemically, ultrasonographically (USG), and cytologically with FNAC. Histopathologic examination (HPE) was done post-surgery. Comparison was done between those with benign and malignant nodules. Correlation was done between pre-operative USG, FNA, and post-operative HPE of the nodules. Results: Out of 322 cases during the study period, the prevalence of clinically detectable thyroid nodule posted for surgery was 39 (12.58%). Most of the patients were euthyroid (94.9%), had nodules in left lobe (41.5%). Most of the nodules were heteroechoic (56.5%) and majority were THY3 nodules (48.7%) on FNAC. On HPE, malignancy was found in 20.5% of the nodules. Compared to benign nodules, malignant nodules were more commonly larger, on the left lobe, solid, hypoechoic, with spiculated margins, punctate calcification, and having associated neck nodes (pall < 0.03). Out of 11 cases, which were radiologically predicted to be malignant, 10 had THY ≥3 on FNA, and 8 were malignant on HPE. USG had a sensitivity, specificity, positive, and negative predictive value of 87.5%, 87.1%, 63.63%, and 96.43% in predicting malignancy. Conclusion: Pre-operative ultrasonography for thyroid nodules can predict malignancy with sufficient sensitivity and specificity and can obviate the need for unnecessary FNAC in many cases and also suggest imminent need for surgery rather than FNAC in very high risk cases.